Dynamic response of composites sandwich plates with carbon nanotubes subjected to blast loading - de Borbon, Fernanda Maria (2012)
An experimental study of the dynamic response of composite aluminum epoxy resin–CNT sandwich plates subjected to blast load is presented in this paper. The sandwich plates consist of aluminum square plates with a core of epoxy resin matrix and 5% in weight of CNT. For comparison purposes, plates with neat epoxy resin core were also tested. Disc shaped plastic explosive (PE4) is used to impart uniform and localized blast loading to the plates. The mass of the explosive is varied to provide a range of response of the sandwich panels from plastic deformation to complete tearing. It was found that the permanent displacement is larger for the plates with CNTs, as for uniform well as localized blast loading, indicating that the inherent brittleness of epoxy resins was overcome by adding CNTs. On the other hand, once the composite material with CNTs has reached the fracture, it is exhibited better energy dissipation behavior than the neat epoxy specimens. Preliminary results show that the failure load is larger for the specimens with CNTs.